2007
DOI: 10.1680/geot.2007.57.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Undrained behaviour of brecciated Upper Lias Clay at Empingham Dam

Abstract: Empingham Dam was built in the early 1970s on a brecciated Upper Lias Clay foundation of fill derived from it. When the dam was designed, the undrained behaviour of intact stiff plastic clay in the field was poorly understood. Thus, a conservative bound to conventional strength tests was adopted to provide an undrained strength profile in the foundation. The shearing resistance of the foundation was also investigated by incorporating an instrumented 24 m high trial bank in the upstream berm of the main dam. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The parameters fit the measured permeability profile with depth employed in previous studies of Kovacevic et al (2007) and Tsiampousi et al (2014). Under the effect of suction, tensile total stresses may lead to instigation of desiccation cracks within the soil, temporarily increasing its overall mass permeability.…”
Section: Soil Properties and Model Parametersmentioning
confidence: 88%
See 1 more Smart Citation
“…The parameters fit the measured permeability profile with depth employed in previous studies of Kovacevic et al (2007) and Tsiampousi et al (2014). Under the effect of suction, tensile total stresses may lead to instigation of desiccation cracks within the soil, temporarily increasing its overall mass permeability.…”
Section: Soil Properties and Model Parametersmentioning
confidence: 88%
“…A cohesion of 7 kPa and an angle of shearing resistance of 23°was adopted, while zero dilation was assumed (see also Table 1). Similar values have been employed in the past by Kovacevic et al (2007). The constitutive model was used in combination with the Imperial College generalized small-strain stiffness model (ICG3SM) of Taborda et al (2016) (model parameters also in Table 1), which is required for the assessment of the slope's serviceability.…”
Section: Soil Properties and Model Parametersmentioning
confidence: 99%
“…There would have been limited change in slope geometry initially, so the stress path moves horizontally; the slope material then failed at peak strength, the slope inclination fell, and the direction of the stress path is reversed to a condition at (or close to) critical state. The critical state parameters for the Upper Lias are probably about c9 ¼ 0, ö9 ¼ 238, the values that Kovacevic et al (2007) found gave the best fit in their modelling of the Empingham dam foundation deformations. At this point there would have been large deformations within the slope as the camber process occurred, and the present-day slope was formed.…”
Section: Evolution: Brecciationmentioning
confidence: 85%
“…The construction of Empingham dam resulted in considerable movement within the dam foundations, which has been analysed by Kovacevic et al (2007), who successfully modelled the movements of the dam, but to do so used strength parameters close to critical state values. The reason why critical state parameters should be appropriate seems to lie in the properties of the brecciated Lias, whose behaviour can be examined in the context of its stress state and strength.…”
Section: Evolution: Brecciationmentioning
confidence: 99%
“…Imperial College has a strong tradition, spanning nearly six decades, of research into embankment dam behaviour, from Bishop's early work on the stability of embankment slopes (Bishop, 1955) to the post-failure analysis and redesign of Carsington dam (Potts et al, 1990;Skempton and Vaughan, 1993) and Vaughan's research into the 'perfect filter' (Vaughan and Soares, 1982), to more recent analysis and redesign of the main dam embankments at Empingham and at Abberton reservoir (Kovacevic et al, 2007(Kovacevic et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%